Hepatitis C Treatment Outcomes for People Who Inject Drugs Treated in an Accessible Care Program Located at a Syringe Service Program. (6th March 2018) - Eckhardt, Benjamin J; Scherer, Matthew; Winkelstein, Emily; Marks, Kristen; Edlin, Brian R
Abstract: Hepatitis C virus (HCV) is a significant public health problem that disproportionately afflicts people who inject drugs. We describe outcomes of HCV treatment co-located within a syringe services program (SSP). Fifty-three participants started therapy, and 91% achieved sustained virologic response. SSPs provide an effective venue for HCV treatment.